2009
DOI: 10.1111/j.1439-0507.2009.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread erosive tinea corporis by Arthroderma benhamiae in a renal transplant recipient: case report

Abstract: Superficial fungal infections are expected to be more prevalent in renal transplant recipients because of graft-preserving immunosuppressive therapy. Here we report the case of a 45-year-old patient with widespread erosive tinea corporis transmitted by domestic animals. Sequencing of the internal transcribed spacer region identified Arthroderma benhamiae (teleomorph of Trichophyton mentagrophytes) in the patient, her husband and her domestic animals. A combination therapy with systemic terbinafine hydrochlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 0 publications
0
24
0
3
Order By: Relevance
“…2,3 Trichophyton species of A. benhamiae can cause tinea capitis, tinea corporis, tinea manuum and tinea faciei, with severe inflammation in children/ adolescents and immunosuppressed patients. 4 Guinea pigs are the most common source of A. benhamiae, but the organism has also been isolated from rabbits, cats and dogs. 3,5,6 In infected guinea pigs, the infection may manifest as circumscribed areas of alopecia with erythema, scaling and crusting, and onychomycosis, with brittle, irregular claws that lack lustre and are unusually coloured.…”
mentioning
confidence: 99%
“…2,3 Trichophyton species of A. benhamiae can cause tinea capitis, tinea corporis, tinea manuum and tinea faciei, with severe inflammation in children/ adolescents and immunosuppressed patients. 4 Guinea pigs are the most common source of A. benhamiae, but the organism has also been isolated from rabbits, cats and dogs. 3,5,6 In infected guinea pigs, the infection may manifest as circumscribed areas of alopecia with erythema, scaling and crusting, and onychomycosis, with brittle, irregular claws that lack lustre and are unusually coloured.…”
mentioning
confidence: 99%
“…Specifically, prednisone causes delayed desquamation and thickening of the stratum corneum, a contributing to the increased incidence and duration of dermatophytosis in patients taking this medication alone or as part of their immunosuppressive regimen. 1 Confounding environmental factors in this patient's case included the use of a super-potent topical steroid, its effect enhanced by occlusion of the area with a glove.…”
Section: Introductionmentioning
confidence: 91%
“…Trichophyton rubrum is the most common cause of dermatophytosis including tinea corporis, tinea pedis, and tinea unguium, regardless of immune status. [1][2][3] Immunosuppressed patients, however, are at an increased for dermatophyte infection, which can become invasive in this population. 1 Lillis et al demonstrated dermatophytosis in 42% of renal transplant recipients, with duration of infection lasting from 15 days up to 10 years.…”
Section: Brief Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque parece que las dermatofitosis no son más frecuentes en estos enfermos que en la población general 7 , en la literatura hay múltiples referencias de infecciones por dermatofitos generalizadas, la mayoría de ellas, en trasplantados renales 8,9 .…”
unclassified